Development of Digital Information Media for the Majapawitra Water Alliance Association to Enhance Engagement - Masnia Ningsih; Rakhmad Saiful Ramadhani; Jenny Yudha Utama (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
The advancement of digital technology has transformed how community organizations communicate, foster participation, and disseminate information to the public. The Aliansi Air Majapawitra Association, a community group dedicated to water resource conservation in Mojokerto, faces challenges in boosting public engagement with its various educational programs and environmental initiatives. This community service project aimed to develop digital information media by optimizing the *aliansiair.com* website and the @aliansi_air_majapawitra Instagram account, serving as platforms for communication, education, documentation, and public interaction. The project methodology encompassed identifying the organization's digital communication needs, content design, website feature development, social media management support, and an initial evaluation of audience response. The results indicate that the developed digital media strengthened the organization's identity, improved access to information regarding water conservation programs, facilitated public access to activity documentation, and encouraged interaction through more structured educational and visual content. The website serves as the organization's information hub, while Instagram functions as a faster, more interactive channel for message dissemination. This development of digital information media contributes to expanding the reach of environmental communication and enhancing opportunities for public involvement in the water resource conservation movement.